Bone-targeted nanoplatform enables efficient modulation of bone tumor microenvironment for prostate cancer bone metastasis treatment - Xiangyu Zhang; Qingbin Liu; Tingting Zhang; Pei Gao; Hui Wang; Lu Yao; Jingwen Huang; Shulong Jiang (Taylor & Francis Group, 2022)
As there is currently no effective therapy for patients with prostate cancer (PCa) bone metastasis, it was stringent to explore the relevant treatment strategies. Actually, the interaction between cancer cells and bone microenvironment plays important role in prostate cancer bone metastasis, especially the Sonic hedgehog protein (SHH) signaling in the bone microenvironment. The SHH promotes osteoblast maturation and osteoblast then secretes RANKL to induce osteoclastogenesis. Herein, this study develops bone-targeting calcium phosphate lipid hybrid nanoparticles (NPs) loaded with docetaxel (DTXL) and SHH siRNA for PCa bone metastasis treatment. For bone targeting purposes, the nanoplatform was modified with alendronate (ALN). (DTXL + siRNA)@NPs-ALN NPs effectively change the bone microenvironment by inhibiting the SHH paracrine and autocrine signaling, enhancing the anti-tumor effects of DTXL. Besides showing good in vitro cellular uptake, the NPs-ALN also inhibited tumor growth both in vitro and in vivo by inducing apoptosis, cell cycle arrest, and autophagy. This DDS comprised of (DTXL + siRNA)-loaded NPs provides an excellent strategy to treat PCa bone metastasis.